Solgerites Reeside, 1932 (Cretaceous Ammonoidea) a synonym of Forresteria Reeside, 1932, with a revision of Solgerites brancoi (Solger, 1904) (Cretaceous Ammonoidea) from Cameroon - Kennedy, W (1985)
A revision of the surviving "Barroisiceras" specimens from Cameroon described by SOLGER (1904) suggests that Barroisiceras brancoi, type species of Solgerites REESIDE, 1932, including varieties mitis and armatus of SOLGER, and Barroisiceras hoberfellneri alstadenensis SOLGER non SCHLüTER are variants of a single species and that Solgerites is a synonym of Forresteria (Forresteria) REESIDE, 1932, of which Eboroceras BASSE, 1947 also is a synonym. © 1985 E. Schweizerbart'sche Verlagsbuchhandlung.